Multiple cutaneous lymphoproliferative disorders showing a retained tumor clone by T‐cell receptor gene rearrangement analysis: a case series of four patients and review of the literature. (12th August 2015) - Stowman, Anne M.; Hsia, Ling‐Lun; Kanner, William A.; Mahadevan, Mani S.; Bullock, Grant C.; Patterson, James W.
Abstract: Background: Mycosis fungoides (MF) is the most common primary cutaneous T‐cell lymphoma (CTCL), followed by CD30+ lymphoproliferative disorders, including lymphomatoid papulosis (LyP) and primary cutaneous anaplastic large cell lymphoma (pcALCL). The objective was to report on a series of patients with different types of CTCL at different times in their clinical course, with a focus on clonality studies. Methods: Four patients with multiple diagnoses of CTCLs were identified. The clinical information, treatment interventions, and histopathology were reviewed. T‐cell receptor (TCR) gene rearrangement studies were performed on all available specimens. Results: The four patients carried diagnoses of: (1) pcALCL and MF; (2) pcALCL, LyP, and pcALCL; (3) LyP, MF, and pcALCL; (4) LyP, pcALCL, and MF; each with characteristic presentation and histopathologic findings. The results of the TCR polymerase chain reaction showed that all tumors expressed and retained a TCR clone(s) as follows: (1) biallelic clone; (2) single clone; (3) biallelic clone with additional clone; and (4) single clone, respectively. Conclusion: We report a series of four cases of individual patients with coexisting diagnoses of some combination of MF, LyP, and pcALCL, whose lesions presented in nontraditional sequence and demonstrated a retained clone by gene rearrangement analysis.